The progeny from the [(T. turgidum X Dasypyrum villosum) amphiploid X Triticum aestivum] hybridization is an effective source of new durum wheat inbred lines - De Pace C.; Bizzarri M.; Vittori D.; Vaccino P.; Caceres M.E.; Ceccarelli M.; Raksegi M.; Vida G. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
The potential of recombination and chromosome elimination in progenies from homoploid hybridization between an amphiploid AdAdBdBdVV and Triticum aestivum AaAaBaBaDD leading to novel durum wheat inbred lines, remains largely unknown. Here, we report the results of homoploid hybridization performed among three AdAdBdBdVV amphiploids (‘M × V’, ‘C × V’, ‘Cr × VB’ obtained, after chromosome doubling of the hybrids from crossing Dasypyrum villosum (Dv) to the T. turgidum ssp durum cvs ‘Modoc’, ‘Capeiti’and ‘Creso’, respectively), and five AaAaBaBaDD bread wheat varieties (‘Agadir’, ‘Chinese Spring’ (‘CS’), ‘Provinciale’, ‘Sagittario’, and ‘Salgemma’) and one inbred line (’41-3’). The average floret fertility upon controlled hybridization was 0.55 (1 caryopsis with F1 embryo every 2 pollinated florets). After selfing, the F1 plants produced caryopses with F2 embryo in 40% of the florets. The chromosome number of the F2 seedlings ranged from 2n=28 to 2n=42. The expected proportion of viable F2 seedlings with 2n=28 was 3.72 × 10-9 while the observed proportion (0.065) was about 7 orders of magnitude higher. The observed frequency of the F2 seedlings with chromosome number 2n>42 was below 0.03, which was in line with the expectation that F2 zygotes with 2n>42 had a very low viability. The expected proportion of such zygotes was 0.57 determining an expected F1 floret fertility of 43%, amazingly close to the observed average floret fertility of the F1 plants. Seven new durum wheat inbred lines have been derived from the ‘M × V’ × ‘CS’ hybridization, two of them (‘5-04’ and ‘13-04’) showing satisfactory agronomic and grain quality traits.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)